2015
DOI: 10.1121/1.4928719
|View full text |Cite
|
Sign up to set email alerts
|

Description and seasonal detection of two potential whale calls recorded in the Indian Ocean

Abstract: Unidentified acoustic signals are recorded by hydrophones placed in the world's oceans. Some of these sounds are suspected to originate from marine mammals. In this study, two acoustic signals recorded by two arrays at Diego Garcia in the northern Indian Ocean are described. Data were available between January 2002 and December 2003. Signals were detected manually using long-term spectral average plots. Time and frequency measurements were taken from a sample of both signals. The first unidentified signal [Die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 49 publications
1
19
1
Order By: Relevance
“…Thus we expect that Omura's whale populations have a relatively high probability of impact from entanglement and bycatch in local fisheries, ship strikes, coastal development and coastal industry. Furthermore, current evidence indicates that populations are non-migratory with local, potentially restricted ranges in low latitude coastal waters, for example as indicated by long-term acoustic monitoring off Madagascar , the Chagos Archipelago (Sousa and Harris, 2015) and northwestern Australia (McCauley, 2009(McCauley, , 2014. Resident populations of cetaceans face different conservation challenges compared to migratory baleen whales; for instance, seasonal restrictions on potential threats (i.e., seismic exploration, shipping lanes, or bycatch-prone fishing gear) are not effective on a resident population that is present year-round.…”
Section: Global Threatsmentioning
confidence: 97%
See 3 more Smart Citations
“…Thus we expect that Omura's whale populations have a relatively high probability of impact from entanglement and bycatch in local fisheries, ship strikes, coastal development and coastal industry. Furthermore, current evidence indicates that populations are non-migratory with local, potentially restricted ranges in low latitude coastal waters, for example as indicated by long-term acoustic monitoring off Madagascar , the Chagos Archipelago (Sousa and Harris, 2015) and northwestern Australia (McCauley, 2009(McCauley, , 2014. Resident populations of cetaceans face different conservation challenges compared to migratory baleen whales; for instance, seasonal restrictions on potential threats (i.e., seismic exploration, shipping lanes, or bycatch-prone fishing gear) are not effective on a resident population that is present year-round.…”
Section: Global Threatsmentioning
confidence: 97%
“…Extensive long-term surveys in the southwest Anakao and northeast Antongil Bay regions indicated no reports of Omura's whale or Bryde's-like animals (Cerchio, personal observation), so the distribution around Madagascar is possibly limited to the central west and northwest coasts. Sousa and Harris (2015) report on two vocalizations of unknown origin off Diego Garcia in the Chagos Archipelago (north and south locations at 6.3 • S and 7.6 • S) attributing them to a baleen whale and speculating they may represent undescribed blue whale vocalizations. One of these, the "Diego Garcia Croak" (DGC), is very similar to Omura's whale song documented off northwest Madagascar (Cerchio et al, 2015), allowing for differences due to signal-to-noise ratio of the available recordings (Figure 4).…”
Section: For Detail) Egyptmentioning
confidence: 98%
See 2 more Smart Citations
“…They observed them at both the H08N and H08S triads, the second component of the Diego Garcia hydroacoustic station. Thus, by visual inspection and comparison with both the signals displayed as type 9 calls by McDonald et al (2006) and the DGD signal of Sousa and Harris (2015), the observed signals are assumed to be type 9 calls and follow both publications in attributing them to blue whales, although no one has yet established a link between these types of signals and a visual observation of blue whales. Although they do not report on the presence of whales with this type of call, four different types of whales have been observed in the Indian Ocean on another set of temporarily deployed hydrophones by Samaran et al (2013), none of which, however, were present in January of 2003 according to their paper.…”
Section: Methods a Test Datamentioning
confidence: 97%